Long-term neurodevelopment outcomes of hand, foot and mouth disease inpatients infected with EV-A71 or CV-A16, a retrospective cohort study. Issue 1 (1st January 2021) - Liang, Lu; Cheng, Yibing; Li, Yu; Shang, Qing; Huang, Jiao; Ma, Caiyun; Fang, Shuanfeng; Long, Lu; Zhou, Chongchen; Chen, Zhiping; Cui, Peng; Lv, Nan; et al.
ABSTRACT: Hand, foot and mouth disease (HFMD) is a common infectious disease in western Asia area and the full range of the long-term sequelae of HFMD remains poorly described. We conducted a retrospective hospital-based cohort study of HFMD patients with central nervous system (CNS) complications caused by EV-A71 or CV-A16 between 2010 and 2016. Patients were classified into three groups, including CNS only, autonomic nervous system (ANS) dysregulation, and cardiorespiratory failure. Neurologic examination, neurodevelopmental assessments, Magnetic Resonance Imaging (MRI) and lung function, were performed at follow up. Of the 176 patients followed up, 24 suffered CNS only, 133 ANS dysregulation, and 19 cardiorespiratory failure. Median follow-up period was 4.3 years (range [1.4–8.3]). The rate of neurological abnormalities was 25% (43 of 171) at discharge and 10% (17 of 171) at follow-up. The rates of poor outcome were significantly different between the three groups of complications in motor (28%, 38%, 71%) domain (p=0.020), but not for cognitive (20%, 24%, 35%), language (25%, 36%, 41%) and adaptive (24%, 16%, 26%) domains ( p  = 0.537, p  = 0.551, p  = 0.403). For children with ventilated during hospitalization, 41% patients (14 of 34) had an obstructive ventilatory defect, and one patient with scoliosis had mixed ventilatory dysfunction. Persistent abnormalities on brain MRI were 0% (0 of 7), 9% (2 of 23) and 57% (4 of 7) in CNS, ANS and cardiorespiratory failure group separately. Patients with HFMD may have abnormalities in neurological, motor, language, cognition, adaptive behaviour and respiratory function. Long-term follow-up programmes for children's neurodevelopmental and respiratory function may be warranted.